2021
DOI: 10.1038/s42003-021-02584-2
|View full text |Cite
|
Sign up to set email alerts
|

Cleaner fish are sensitive to what their partners can and cannot see

Abstract: Much of human experience is informed by our ability to attribute mental states to others, a capacity known as theory of mind. While evidence for theory of mind in animals to date has largely been restricted to primates and other large-brained species, the use of ecologically-valid competitive contexts hints that ecological pressures for strategic deception may give rise to components of theory of mind abilities in distantly-related taxonomic groups. In line with this hypothesis, we show that cleaner wrasse (La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…One possibility is that Dualism is strictly a social invention that arises via cultural transmission alone. On an alternative account ( 1 ), Dualism emerges naturally, from the tension between two intuitive systems of core knowledge that are evident in young infants ( 30 , 31 ), and arguably, nonhuman animals ( 32 39 ).…”
mentioning
confidence: 99%
“…One possibility is that Dualism is strictly a social invention that arises via cultural transmission alone. On an alternative account ( 1 ), Dualism emerges naturally, from the tension between two intuitive systems of core knowledge that are evident in young infants ( 30 , 31 ), and arguably, nonhuman animals ( 32 39 ).…”
mentioning
confidence: 99%
“…Remarkably complex behaviors (tool use in the case of C. anchorago and T. hardwicke, 17,18 and social cognition in the case of L. dimidiatus [19][20][21] ) have been reported in the group of wrasses. Cichlids are phylogenetically close to wrasses and display relatively complex social and cognitive behaviors, although no instances of tool use have been observed [22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably complex behaviors (tool use in the case of C. anchorago and T. hardwicke (Bernardi, 2012; Paśko, 2010), and social cognition in the case of L. dimidiatus (Kohda et al, 2022; McAuliffe et al, 2021; Wismer et al, 2016)) have been reported in the group of wrasses. Cichlids are phylogenetically close to wrasses and display relatively complex social and cognitive behaviors, although no instances of tool use have been observed (Barks and Godin, 2013; Hotta et al, 2019; Schluessel et al, 2022; Snekser and Itzkowitz, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing number of examples of advanced cognitive capacity in fishes ( 47 , 48 ). Cleaner fish have emerged as a model system for the study of such advanced cognition, including perspective taking that is related to ToM ( 49 ). Nevertheless, there is no compelling reason to suspect that cleaner fish are exceptional within vertebrates or even within fish with respect to the underlying cognitive mechanisms allowing MSR ability (but see ref.…”
Section: Discussionmentioning
confidence: 99%